Giant lung cysts following necrotizing pneumonia: Resolution with conservative treatment. Issue 6 (21st March 2019) - Gross, Itai; Gordon, Oren; Cohen‐Cymberknoh, Malena; Reiter, Joel; Tsabari, Reuven; Gileles‐Hillel, Alex; Erlichman, Ira; Hevroni, Avigdor; Shoseyov, David; Kerem, Eitan
Abstract: Rationale: Necrotizing pneumonia is characterized by destruction and liquefaction of the lung tissue and loss of the normal pulmonary parenchymal architecture. During the course of resolution areas of hyperlucency are formed, sometimes with the development of giant lung cysts that can be a field with fluid resembling lung abscess. There is no consensus on the management of these abnormalities. Objective: To assess the prevalence of giant lung cysts as a complication of necrotizing pneumonia and to report our experience with conservative treatment that achieved complete resolution. Methods: Medical chart reviews of all children aged 0 to 18 years hospitalized with necrotizing pneumonia in a single tertiary center from 2015 to 2017, demographic data, and clinical course during and after hospitalization as well as serial chest imaging were collected. Results: During the study period, 761 children were diagnosed with community‐acquired pneumonia, 16 of 761 (2.3%) had necrotizing pneumonia and 6 of 16 (37.5%) with necrotizing pneumonia complicated by a giant lung cyst or lung abscess. All were closely observed and showed complete clinical and radiographic resolution with antibiotic treatment. Conclusions: Treatment of giant lung cyst formation following necrotizing pneumonia by a conservative approach with prolonged antibiotics results in complete recovery with no need for invasive procedures.